Strategi Rebranding Riche Heritage Hotel Malang melalui Instagram @hotelriche - Agnes Kristika Setianing; Indra Novianto Adibayu (Universitas Merdeka Malang, 2024)
Hotels are one of the considerations for visitors to a city. Riche Hotel is one of the hotels in Malang City which was awarded a cultural heritage building by the Malang City Government. This research uses a qualitative approach, with descriptive research methods. The data collection and analysis technique uses the concept of source triangulation, namely by conducting interviews with 3 informants from Riche Hotel Malang. This research aims to explain the rebranding strategy carried out by Riche Hotel Malang via Instagram. The research results show that Riche Hotel Malang carried out 4 stages of rebranding, namely repositioning by introducing Hotel Riche Malang as a contemporary, family-friendly and strategic hotel. Then at the renaming stage there were no changes, as well as redesigning the shape of the rooms, and relaunching by holding a launching event for the new style of Hotel Riche Malang and collaborating with local influencers in Malang City.